2016
DOI: 10.5155/eurjchem.7.3.368-374.1443
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural characterization and biological properties of Cu(II), Ni(II), Mn(II), Zn(II) and VO(II) complexes of tetradentate Schiff bases

Abstract: New binucleating Cu(II), Ni(II), Mn(II), Zn(II) and VO(II) complexes of the prepared ligands with N4 donor were synthesized. The ligands are obtained by the condensation of paraphenylenediamine with diacetylmonoxime and benzilmonoxime. The synthesized ligands and their metal complexes were characterized by elemental analysis and various spectroscopic techniques. The Cu(II), Ni(II) complexes were square planar, VO(II) complex was square pyramidal, whereas Mn(II), Zn(II) complexes were of tedrahedral geometry. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Vibrational spectra of the compounds was recorded in Bruker Tensor 27 in the range of 4000-400 cm -1 . 1 H & 13 C NMR spectra were recorded on the Bruker 300 Hz spectrometer using DMSO-d 6 as a solvent. Mass spectrum was recorded for the L 1 , ML 1 & ML 1 L 2 using 410 Prostar Binary LC with 500MS IT PDA Detectors.…”
Section: Methodsmentioning
confidence: 99%
“…Vibrational spectra of the compounds was recorded in Bruker Tensor 27 in the range of 4000-400 cm -1 . 1 H & 13 C NMR spectra were recorded on the Bruker 300 Hz spectrometer using DMSO-d 6 as a solvent. Mass spectrum was recorded for the L 1 , ML 1 & ML 1 L 2 using 410 Prostar Binary LC with 500MS IT PDA Detectors.…”
Section: Methodsmentioning
confidence: 99%
“…These metal complexes can potentially exhibit enhanced antioxidant capabilities, such as flavonoid complexes that have demonstrated superior efficiency in radical inhibition. To further enhance the antioxidant prowess of OXY, we propose its complexation with transition metals. A diverse array of geometries, coordination numbers, and oxidation states can be achieved. , The selection of the metal and the choice of mechanism play a significant role in boosting antioxidant capacity. , Experimental and theoretical studies have identified two well-distinct complexation mechanisms: direct chelation and coupled-deprotonation-chelation, with the latter being considered more plausible. , Copper complexes have attracted significant interest due to their remarkable anticancer and antioxidant properties, surpassing those of nickel, cobalt, and zinc complexes. Encouraging outcomes from joint experimental and theoretical studies on copper-resveratrol complexes , have motivated us to explore the complexation of OXY with copper in its two oxidation states, Cu + and Cu 2+ . To the best of our knowledge, complexes of Cu + and Cu 2+ with the ligand Resveratrol substituted by OH in position (5′) have not been determined experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond its applications in organic synthesis, α-benzilmonoxime has found utility in research endeavors aimed at exploring reaction mechanisms, kinetics, and other facets of organic chemistry [4][5][6]. Furthermore, investigations into certain compounds related to α-benzilmonoxime have been conducted to assess their potential biological activity [7][8][9]. However, obtaining specific details on this aspect may necessitate consulting the most recent scientific literature.…”
Section: Introductionmentioning
confidence: 99%